Effect of silicate doping on the structure and mechanical properties of thin nanostructured RF magnetron sputter-deposited hydroxyapatite films; Surface and Coatings Technology; Vol. 275 - Surmeneva M. A. Maria Alexandrovna; Mukhametkaliev T. M. Timur Mukhamedrashidovich; Tyurin A. I. Aleksandr Ivanovich; Teresov A. D. Anton Dmitrievich; Koval N. N. Nikolay Nikolaevich; Pirozhkova T. S. Tatjyana Sergeevna; Shuvarin I. A. Ivan Aleksandrovich; Shuklinov A. V.; Zhigachev A. O.; Oehr C.; Surmenev R. A. Roman Anatolievich (2015, 2015)
Title screen